2019
DOI: 10.1177/1367493519882850
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of parenting interventions for child chronic health conditions

Abstract: This systematic review summarizes the parenting intervention literature for parents of children with chronic health conditions and evaluates intervention effects on parenting (parenting skills and parenting efficacy) and child (behaviour, illness severity/control and quality of life) outcomes. Systematic searches using seven electronic databases (including CINHAL, MEDLINE and PsycINFO) were used to identify relevant papers published in English between 1997 and 2017, and reference lists were searched for additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 68 publications
2
33
0
1
Order By: Relevance
“…[29][30][31][32] Intervention should be brief and cost-effective so as not to place additional burden on already under-resourced families and could include systemic family therapy (to address family dynamics) and/or behavioral parenting interventions (problem solving, communication, positive parenting, and stress management skills). 33,34 Health professionals within the child's medical team (clinical psychologists or social workers) can also assist families by providing such interventions, identifying existing social supports, referral to community organizations and support groups, and facilitating positive communication between health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Intervention should be brief and cost-effective so as not to place additional burden on already under-resourced families and could include systemic family therapy (to address family dynamics) and/or behavioral parenting interventions (problem solving, communication, positive parenting, and stress management skills). 33,34 Health professionals within the child's medical team (clinical psychologists or social workers) can also assist families by providing such interventions, identifying existing social supports, referral to community organizations and support groups, and facilitating positive communication between health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review (Morawska et al, 2020) has indicated that EBPSs may lead to improved parent selfefficacy, parenting behaviour, illness severity/control, child quality of life and child behaviour; however, intervention effects were mixed and confined to parent-report outcome measures.…”
Section: Domains/outcome Areas Brief Commentarymentioning
confidence: 99%
“…In this type of family context, CYAs can experience negative health outcomes including stress and poor adjustment, poorer coping skills, and higher hospitalization rates [ 13 , 21 ]. To support these parents, parenting support programs based on preventive psychology could reduce emotional fragility in parents of CYAs with chronic conditions [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%